Early identification of patients with Chagas disease at risk of developing cardiomyopathy using 2-D speckle tracking strain: Win, Miranda prediction of Chagas cardiomyopathy. (August 2022) - Win, Sithu; Miranda-Schaeubinger, Monica; Gustavo Durán Saucedo, Ronald; Carballo Jimenez, Paula; Flores, Jorge; Mercado-Saavedra, Brandon; Camila Telleria, Lola; Raafs, Anne; Verastegui, Manuela; Bern, Caryn; Tinajeros, Freddy; Heymans, Stephane; et al.
Highlights: What is already known about this subject? Speckle-tracking strain echocardiography (STE) is added to conventional echocardiography and has been shown to detect subclinical myocardial contractile dysfunction before a reduction in LVEF. What does this study add? In this study, we evaluate the utility of LV STE for predicting worsening CCC in patients with Chagas disease. How might this impact on clinical practice? Screening for changes in STE-based Global Longitudinal Strain (GLS) may provide a non-invasive approach to identify patients who could benefit from earlier management, such as more frequent follow-up or initiation of treatment. Abstract: Background: Chagas disease is an endemic protozoan disease with high prevalence in Latin America. Of those infected, 20–30% will develop chronic Chagas cardiomyopathy (CCC) however, prediction using existing clinical criteria remains poor. In this study, we investigated the utility of left ventricular (LV) echocardiographic speckle-tracking global longitudinal strain (GLS) for early detection of CCC. Methods and results: 139 asymptomatic T. cruzi seropositive subjects with normal heart size and normal LV ejection fraction (EF) (stage A or B) were enrolled in this prospective observational study and underwent paired echocardiograms at baseline and 1-year follow-up. Progressors were participants classified as stage C or D at follow-up due to development of symptoms of heart failure, cardiomegaly, or decrease in LVEF. LV GLS was calculated as the average peak systolic strain of 16 LV segments. Measurements were compared between participants who progressed and did not progress by two-sample t -test, and the odds of progression assessed by multivariable logistic regression. Of the 139 participants, 69.8% were female, mean age 55.8 ± 12.5 years, with 12 (8.6%) progressing to Stage C or D at follow-up. Progressors tended to be older, male, with wider QRS duration. LV GLS was −19.0% in progressors vs. –22.4% in non-progressors at baseline, with 71% higher odds of progression per +1% of GLS (adjusted OR 1.71, 95% CI 1.20–2.44, p = 0.003). Conclusion: Baseline LV GLS in participants with CCC stage A or B was predictive of progression within 1-year and may guide timing of clinical follow-up and promote early detection or treatment.